Fiction and Epistemic Value: State of the Art. (4th June 2022) - Green, Mitchell
Abstract: We critically survey prominent recent scholarship on the question of whether fiction can be a source of epistemic value for those who engage with it fully and appropriately. Such epistemic value might take the form of knowledge (for 'cognitivists') or understanding (for 'neo-cognitivists'). Both camps may be sorted according to a further distinction between views explaining fiction's epistemic value either in terms of the author's engaging in a form of telling, or instead via their showing some state of affairs to obtain, a special case of which is the provision of self-knowledge. Fictional works that show rather than tell often employ thought experiments. The epistemic value of some fictional works is indicated by their enabling of empathy, itself illuminated via the psychological process of experience-taking. Whether a fictional work offers epistemic value by telling or showing, there is, in principle, no bar to its being able to deliver on what it offers, and consumers of fiction who exercise epistemic vigilance may gain either knowledge or some degree of understanding from their engagement with it.